Nursery Assistants' Performance and Knowledge on Cardiopulmonary Resuscitation: Impact of Simulation-Based Training - Beaufils, Fabien; Ghazali, Aiham; Boudier, Bettyna; Gustin-Moinier, Valérie; Oriot, Denis (Frontiers in Pediatrics, 2020)
Background: Child cardiac arrest is rare, but more frequent among infants, requiring immediate cardiopulmonary resuscitation (CPR). Many studies have reported that simulation-based training (SBT) increased CPR performance of healthcare providers. However, the CPR performance of laypeople using basic life support remains poorly known. The aim of this study was to assess nursery assistants’ (non-healthcare providers) CPR performance and knowledge, before and after SBT. Methods: The study was carried out from January to June 2018 in the city of Poitiers, France. Two teaching sessions (T1 and T2) and two evaluation sessions (E1 and E2) were performed. Performance in infant CPR on a manikin at E1 and E2 were videotaped and assessed automatically with Resusci Baby QCPR® and a SimPad PLUS SkillReporter (QCPR Global Score and skills) and by an observer using an original CPR performance checklist (MCPR Global-Score and skills). Nursery assistant’s CPR knowledge was assessed by a questionnaire at the beginning and the end of the session T1, E1 and E2. Results: 27 nursery assistants over 30 contacted were included. There was an improvement between E1 and E2 in QCPR Global-Score (E1: 42.4±23.6% vs E2: 55.1±23.7%, p=0.032), MCPR Global-Score (E1: 50.0+11.9% vs E2: 72.3+8.5%; p<0.001) and theoretical knowledge with score (over 45) of 16.9+5.4 before T1 and 35.2+2.7 after E2 respectively (p<0.001). The improvement mainly concerned QCPR and MCPR compression steps scores. MCPR Global-Score was strongly correlated to QCPR Global-Score (r=0.61; p<0.01) and predictive to CPR quality determined by QCPR Global-Score (AUC=0.77; p<0.01) with a high sensitivity and negative predictive values. Moreover, these improvements were maintained two months after training with no difference between scores obtained by the three groups 15, 30 or 60 days after simulation-based training session T2. Conclusion: SBT could significantly improve knowledge and skills in infant CPR management by nursery assistants especially for chest compression. CPR performance checklist appeared as an interesting tool to assess CPR performance quality.